Prevalence and risk factors of irritable bowel syndrome in adolescents - Muzal Kadim (Indonesian Pediatric Society Publishing House, 2021)
Background Irritable bowel syndrome (IBS) is a common gastrointestinal disorder in children and adults. The IBS is diagnosed by symptoms that fulfill the Rome IV criteria. This condition can impact quality of life, especially in adolescents.